Closed loop microfluidic platform based on domain wall magnetic conduits: a novel tool for biology and medicine. Issue 1686 (21st November 2014) - Fan, R.; Huang, T.J.; Huang, Y.; Shi, Q.; Monticelli, M.; Petti, D.; Albisetti, E.; Cantoni, M.; Guerriero, E.; Sordan, R.; M.Carminati; Ferrari, G.; et al.
ABSTRACT In this paper we present an innovative on-chip platform suitable for the simultaneous manipulation and detection of the transit of a single magnetic bead. This system is based on the controlled displacement of constrained magnetic domain walls (DWs) that are used to move and sense particles in suspension over the chip. To this scope, the high stray field from the transverse DWs created at the corners of ferromagnetic zig-zag structures is used for particles manipulation, while electrical contacts flanking a single corner are employed to simultaneously monitor the DW passage through that corner, via anisotropic magneto resistance (AMR) measurements. A single DW carrying a magnetic particle is nucleated and manipulated within the zig-zag shaped magnetic conduit, trough the action of external magnetic fields. At the same time, the variation of the voltage drop across a corner flanked by a pair of electrical leads is measured, allowing to detect the transit of the DW thanks to the change of the relative orientation of current and spins at the corner related to the peculiar micromagnetic configuration of the DW (AMR). Work is in progress in order to selectively distinguish the transit of a naked DW from that of a DW bound to a magnetic particle. This work paves the way to the development of a closed-loop microlfuidic platform for on-chip bead manipulation, where single bead can be finely moved and their motion continuously checked, via AMR electrical detection and without need of optical monitoring, in a fully integrated closed-loop system.